A parallel coupled-line bandpass filter / Muhd Nur Azzammuddin Abdullah - Abdullah, Muhd Nur Azzammuddin (2011)
In this paper, a bandpass filter using parallel coupled resonators was designed at centre frequency of 5.8 GHz using Butterworth method. The filter was implemented on the epoxy laminate with relative permittivity, er = 3.48 with substrate thickness 1.524 mm. All the designing and simulation of the filter was carried out with the aid of electromagnetic simulator. Comparisons between measured and simulated values of the parameter of the filter were carried out and it was observed that all these values were very close with each other.